1968
DOI: 10.1007/bf00586149
|View full text |Cite
|
Sign up to set email alerts
|

Larvengestalt und Eingeweide-Situs beim Alpenmolch (Triturus alpestris) nach halbseitiger UV-Bestrahlung von Neurula- und Nachneurula-Keimen

Abstract: Neurulae and postneurulae ofTriturus alpestris (up toHARRISON stage 29) were irradiated with mixed ultraviolet light from the left, right, dorsal or ventral side, respectively. The duration of treatment ranged from 1-600 seconds. Visible effects occurred already after a 5 sec irradiation. Embryos and larvae showed defects of histological and external features. In this paper "inversions" are distinguished from "partial inversions". In "inversions" the curvature of the gut and the liver sinus (or, in some cases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1968
1968
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Physical interference can also influence asymmetries. Treatment with X-rays increases the percentage of situs inversus in newts , as does unilateral ultraviolet radiation (von Kraft, 1968a) and also electric current (von Kraft, 1968b). If plaice larvae are prevented from settling by agitation of the water, metamorphosis does not occur, and they remain symmetrical (Agassiz, in Osborn, 1894).…”
Section: R E F E R E N C E Smentioning
confidence: 99%
“…Physical interference can also influence asymmetries. Treatment with X-rays increases the percentage of situs inversus in newts , as does unilateral ultraviolet radiation (von Kraft, 1968a) and also electric current (von Kraft, 1968b). If plaice larvae are prevented from settling by agitation of the water, metamorphosis does not occur, and they remain symmetrical (Agassiz, in Osborn, 1894).…”
Section: R E F E R E N C E Smentioning
confidence: 99%
“…Of primary importance for the development of later organ asymmetry is a specific process of determination, which starts with gastrulation and finishes during neurulation. During this "determination phase" (von Kraft 1971a) the embryo is still morphologically completely bilaterally symmetrical and shows no apparent left-right gradient of development This is also true for a subsequent "post-determination phase" (von Kraft 1971a), in which influencing the future organ asymmetry is no longer possible (von Woellwarth 1950;Wehrmaker 1969;von Kraft 1968a;1970;1971c, 1973.…”
Section: By Arne Von Kraftmentioning
confidence: 96%
“…At least in Urodeles it was shown that all kinds of transient form s between the norm al situs and the situs inversus can occur, so that a continuous situs spectrum can be achieved (von Kraft, 1968a(von Kraft, , 1969b(von Kraft, , 1970(von Kraft, , 1971b . For different reasons the am phibian em bryo was preferred as an experim ental model, and most experiments on organ asym m etry and the left±right problem in organ ogenesis have been perform ed with these animals (Oppenheim er, 1974).…”
Section: Introductionmentioning
confidence: 97%